As experiências nos lugares turísticos: um olhar sobre os projetos Quarta do Tambor de Crioula e Pôr do Sol no Palácio - SANTOS, Dorilene Sousa (2020)
In the current scenario of tourism research, one of the questions presented is based on the evolution of the services paradigm to the experiences paradigm. According to this new model, tourists would be looking for memorable experiences and active participation in the places visited. This model, known as tourism of experience or experiential tourism, is seen as a strategy for formatting new products in tourism, respecting the authenticity of the local culture. In this sense, this work had as main objective to verify if there is application of the dimensions of the tourist experiences in the Tambor de Crioula's Wednesday and Sunset at the Palace projects , in the Historic Center of São Luís - MA. It is an exploratory research, which was based on a bibliographic and documentary methodological process, as well as on the use of semi-structured interviews, as a data collection instrument, with the purpose of articulating the information obtained with the theoretical framework addressed, identifying the dimensions and characteristics of the tourist experience. The concept of experience is discussed, especially focused on the studies of Walter Benjamin (1989; 2012), and Yi-Fu Tuan (2013) and the relationship of this concept with tourism. Individual and collective memory are also discussed, based on authors such as Joel Candau (2016), Jacques Le Goff (1992) and Michael Pollak (1989; 1992). For debates related to tourism and the role of the community in the activity, authors were sought, such as Beni (2006), Cooper (2011), Dias (2005; 2003) and Urry (2001). With regard to issues related to tourist experiences and dimensions of experiences, authors such as Pine II and Gilmore (1999), Marujo (2016), Trigo (2010) and Oh, Fiore and Jeoung (2007) were investigated in the literature. Based on the reports of the 95 (ninety-five) project participants, interviewed in this research, it is possible to understand the perceptions generated through the dimensions of their experience (entertainment, aesthetics, education, escapism), showing that the applicability from tourist experiences to tourism goods and services can contribute or result in the expansion of knowledge, in addition to providing memorable moments for tourists and the community.